Clinical management of finger joint capsulitis/synovitis in a rock climber - Jared Vagy (Frontiers Media S.A., 2023)
This case study presents a 23-year-old male recreational rock climber, who climbed an average of 3-4 times per week and presented with finger joint capsulitis/synovitis after increasing his climbing intensity and training from moderate to high over 6 months, which led up to injury. During the exam, the diagnosis was ruled in with clinical orthopedic testing. Additional movement analyses revealed improper gripping mechanics contributing to asymmetric finger loading. A comprehensive rehabilitation program was developed based on the concept of a progressive framework that included unloading of the affected tissues, increasing mobility, improving muscle performance, and correcting suboptimal climbing movements. After 6 weeks, the climber's pain 24 h after climbing, which was rated on a visual analog pain scale (VAS), decreased from 5.5/10 to 1.5/10 and 0/10 at the 12-month follow-up. His patient-specific functional scale improved from 0% at the initial evaluation to 43% after 6 weeks and to 98% after 12 months. His sports-specific disabilities of the arm, shoulder, and hand improved from 69% to 34% to 6% during the initial evaluation, 6-week follow-up, and 12-month discharge. He made a full recovery to his previous grade of V8 bouldering. This is the first case study of its kind to provide a rehabilitation framework for the management of finger joint capsulitis/synovitis in a rock climber.